Emotion dysregulation and deliberate self-harm in adolescents - Andi Tenri Faradiba; Anindya Dewi Paramita; Rita Puspa Dewi (Universitas Negeri Padang, 2022)
Adolescents belong to the high-risk group for deliberate self-harm. Data shows that about 20 percent of teenagers in the world engage in self-injurious behavior in forms of scratching, razor blading, hitting, biting, hair-grabbing, and head-banging against walls just to relieve pain. This study aims to determine the correlation between emotion dysregulation and deliberate self-harm in adolescents. This study applied two instruments to measure each variable: (1) Difficulties in Emotion Regulation Scale (DERS), developed by Victor and Klonsky (2016), to measure emotion dysregulation; and (2) Deliberate Self-Harm Inventory, developed by Gratz (2001), to measure deliberate self-harm. Researchers implemented a quantitative approach with a correlational design to answer the research questions. Participants were 174 adolescents recruited from the distribution of online questionnaires with purposive sampling technique. Findings from the study indicate that emotion dysregulation is positively correlated with deliberate self-harm in adolescents with a sig p value < 0.005. This research concludes that the higher the emotion dysregulation, the higher the deliberate self-harm in adolescents.